Ataxic gait. Issue 7 (6th July 2021) - Bhaskar, Shalini; Tengku Kamadjaja Aziz, Tengku Ahmad Hidayat; Paramajothy, Vanita
Abstract: Ataxia as the main complaint in a young patient prompts to diagnose neurodegenerative diseases. Not all ataxias are irreversible. We present a video of a patient in the clinic with ataxia diagnosed as subacute combined degeneration of the cord. Abstract : Ataxia as the main complaint in a young patient prompts to diagnose neurodegenerative diseases. Not all ataxias are irreversible. We present a video of a patient in the clinic with ataxia diagnosed as subacute combined degeneration of the cord.